(untitled) (International Journal of Physiotherapy, 2015)
Background:A temporo-mandibular joint dysfunction or TMD is a group of conditions characterized by pain in the muscles of mastication, the temporo-mandiblar joint or both. Rocabado has described techniques includes the Rocabado’s manipulation and Rocabado’s exercises which have both been individually advocated for treatment of TMD. The purpose of study is to determine the effectiveness of Rocabado’s techniques on TMJ dysfunction symptoms, pain, TMJ Range of Motion (ROM) and jaw functional limitation for subjects with temporo-mandibular joint dysfunction. Method: Pre to post test experimental study design, subjects with temporo-mandibular joint dysfunction randomized into two groups with 15 subjects into each group with total of 30 subjects in Study and control group, respectively. The study group received the Rocabado’s technique which consisted of Rocabado’s non-thrust TMJ manipulation and Rocabado’s exercises along with conventional TMJ exercises and the control group received only conventional TMJ exercises. The exercises were performed for 6 times per each session, six times in a day, one session under supervision and remaining five sessions by the subject at home for 6 days in a week for duration of 2 weeks. The outcome measurements such as VAS for pain, TMJ ROM, Fonseca’s questionnaire rating for TMJ dysfunction symptoms and jaw function limitation score (JFLS) was measured before and after two weeks of intervention. Results: Comparative analysis, using Independent ‘t’ test and Mann Whitney U- test found that the means of VAS, TMJ ROM, Fonseca’s questionnaire and JFLS scores showed statistically significant difference (p <0.05) when the pre-intervention means and post-intervention means were compared between two groups. Conclusion: It is concluded that Rocabado’s technique found to have statistically and clinically significant added effect with conventional TMJ exercises shown greater percentage of improvements obtained in reducing TMJ dysfunction symptoms, pain, jaw functional limitation and increasing TMJ ROM comparing with only conventional TMJ exercises in subjects with Temporamandibular joint dysfunction with restricted mouth opening mobility.